Sistem Pengukuran Tinggi dan Berat Badan Berdasarkan Perhitungan Body Surface Area (BSA) Menggunakan Boundingbox Berbasis Raspberry Pi - Mohammad Isya Alfian; Hurriyatul Fitriyah; Fitri Utaminingrum (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
BSA (Body Surface Area) is used as a way to get information on a person's body condition. Paramedics use these calculations in patient data collection and require a long time. In previous studies using image processing techniques to speed up data retrieval. Data retrieval is carried out front and side view then processed using pixels by cropping the image. From these studies, researchers have the idea of using a mini pc to further speed up data retrieval and be efficient. BSA calculations are included in the mini pc Raspberry Pi and assisted by webcam cameras as image takers. This tool is useful to help paramedics to collect data on body weight and height, faster and more efficiently. The object of the research that was sampled was 20 people, male and female, consisting of children and adults. Data collection was carried out 22 times each in children and adults. The data obtained is calculated by the Bounding Box accuracy value. The results of height accuracy in boys were 91.4%, girls were 87.8%, male adults were 98.34%, and female adults were 98.2%. While the results of accuracy for weight are based on the k value of each object. The k value for boys is 1.34 with an accuracy of 75.32%, girls 1.34 with an accuracy of 79.76%, male adults 1.26 with an accuracy of 95.6%, and adult women 1 , 22 with an accuracy of 92.38%.